PENGARUH TEMUAN AUDIT, OPINI AUDIT DAN TRANSPARANSI TERHADAP TINGKAT KORUPSI - Siti Triya Setia Ningsih; Haryanto Haryanto (Diponegoro Journal of Accounting, 2022)
This study aims to determine the effect of audit finding, audit opinion and transparency on the corruption. In this study the dependent variable consisting of Corruption. The independent variable in this study is audit finding, audit opinion and transparecy. This research was conducted with secondary data, namely multiple liniear regression analysis. The data collection sourced from BPK related to IHPS and LHP LKPD. High Court related to data of criminal acts of corruption and local government website reltaed to transparency data. The results showed that audit findings, audit opinion and transparency have no effect on the level of corruption in both districts and cities in Central Java Provinces.